Nursing before and after COVID-19: Outflows, Inflows and Self-Employment - Guyonne Kalb; Jordy Meekes (Institute of Labor Economics (IZA), 2024)
We study nurses' labour dynamics in light of continuing nurse shortages and the COVID-19 pandemic. Using Dutch monthly administrative microdata, all nursing-qualified persons observed in January 2016 and/or in January 2020 are compared and followed for one year before and three years after both baseline months. Compared to the 2016 Cohort, women and men in the 2020 Cohort who were employed in the healthcare sector at baseline were 0.3 and 1 percentage point more likely to have left employment; and, conditional on still being employed, 0.8 and 1.2 percentage points more likely to have left healthcare employment after three years. The 2020 Cohort women and men were also 1 and 1.7 percentage points more likely to transition from salaried employment to self-employment, and they reduced working hours by 0.6% and 1.5% more by December 2022. Except during COVID outbreaks, there is no higher inflow into healthcare employment by nursing-qualified women and men who were not employed in healthcare at baseline. Finally, other healthcare professionals fared better, with similar healthcare sector retention rates in 2019-2022 compared with 2015-2018. Overall, the pandemic accelerated nurse shortages through reduced retention and increased self-employment, and its impact is still felt at the end of 2022.
Keywords: I11; J16; J20; J44; J62; 330; nurses; labour dynamics; self-employment; healthcare; gender; COVID-19